1999
DOI: 10.1037/0022-0663.91.2.284
|View full text |Cite
|
Sign up to set email alerts
|

Who said what? Source memory for narrator and character agents in literary short stories.

Abstract: One dimension of reading literacy involves the tracking of agents associated with the text. In a literary short story, there is a society of character agents and pragmatic agents. This study investigated the relative salience of different classes of agents in memory. Two experiments measured source memory as an index of agent salience in long-term memory. Patterns of source memory scores supported an invisible third-person narrator hypothesis and an agent amalgamation hypothesis, but not a structural prominenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 58 publications
1
11
1
Order By: Relevance
“…We are interested in the identity rather than the credibility of the source. Previous research on source identity found better source memory for stories with a first person narrator (e.g., "I came home and poured myself a Scotch") than a third person narrator (e.g., "He came home and poured himself a Scotch"; Graesser, Bowers, Olde, & Pomeroy, 1999;Graesser, Millis, & Zwaan, 1997). This finding is neutral with regard to the question whether speech type affects source memory as the use of direct and indirect speech does not depend on a specific narrator perspective.…”
contrasting
confidence: 50%
“…We are interested in the identity rather than the credibility of the source. Previous research on source identity found better source memory for stories with a first person narrator (e.g., "I came home and poured myself a Scotch") than a third person narrator (e.g., "He came home and poured himself a Scotch"; Graesser, Bowers, Olde, & Pomeroy, 1999;Graesser, Millis, & Zwaan, 1997). This finding is neutral with regard to the question whether speech type affects source memory as the use of direct and indirect speech does not depend on a specific narrator perspective.…”
contrasting
confidence: 50%
“…De Pereyra, Britt, et al (2014), for example, have reported that readers remember sources involved in the situation (e.g., a witness) better than remote sources (e.g., someone commenting the topic from a distance). A similar effect has also been reported by Graesser, Bowers, Olde, and Pomeroy (1999) regarding the representation of agents associated with a text. At the same time, we cannot rule out the possibility that source-to-source linking develops strategically during reading under some conditions.…”
Section: Limitationssupporting
confidence: 65%
“…In support of this prediction, Graesser and his colleagues have shown that a narrative agent's salience in the discourse mediates the extent to which readers monitor their knowledge states (Graesser, Bowers, Olde, White, & Person, 1999) and remember their dialogue (Graesser, Bowers, Olde, & Pomeroy, 1999). Although Graesser's research is relevant to the present study and this prediction, it is important to note that they did not study character goals.…”
Section: Factors That Influence the Monitoring Of A Character's Goalsmentioning
confidence: 53%
“…Despite the fact that most narratives contain multiple characters interacting in a story world, relatively little research has been done that assesses the extent to which understanders monitor the concerns and construct elaborate representations of multiple characters (see Graesser, Bowers, Olde, & Pomeroy, 1999;Graesser, Bowers, Olde, White, & Person, 1999;Trabasso & Nickels, 1992). Although it seems reasonable that narrative understanding and appreciation require viewers and readers to keep track of multiple characters' goals, it is also likely that working memory constraints place limitations on one's ability to do so.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation